2002
DOI: 10.1603/0022-2585-39.5.736
|View full text |Cite
|
Sign up to set email alerts
|

Repellent Activities of Stereoisomers ofp-Menthane-3,8-diols AgainstAnopheles gambiae(Diptera: Culicidae)

Abstract: Four stereoisomers of p-menthane-3,8-diol, which make up the natural product obtained from Eucalyptus citriodora, were synthesized through stereoselective procedures. Repellency assays showed that all the four were equally active against Anopheles gambiae s.s. Racemic blends and the diastereoisomeric mixture of all the four isomers were also equally repellent. 1-alpha-terpeneol, with a single hydroxyl function at C-8 and unsaturation at C-8, and menthol, with a single hydroxyl function at C-3, were not repelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 15 publications
1
42
0
2
Order By: Relevance
“…This valuable component may be present in only low concentrations (< 1 %), or even trace amounts, in the essential oils of E. citriodora, and therefore would need to be synthesized 12 . In the present study, we have shown that plants grown under shaded conditions produced record amounts of (±)-p-Menthane-3,8-diol (3.93-4.66 %), whereas those grown under 'full sun' produced significantly lower amounts (0.67 %) and in only some of the plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This valuable component may be present in only low concentrations (< 1 %), or even trace amounts, in the essential oils of E. citriodora, and therefore would need to be synthesized 12 . In the present study, we have shown that plants grown under shaded conditions produced record amounts of (±)-p-Menthane-3,8-diol (3.93-4.66 %), whereas those grown under 'full sun' produced significantly lower amounts (0.67 %) and in only some of the plants.…”
Section: Discussionmentioning
confidence: 99%
“…E. citriodora is grown extensively worldwide, mainly for the paper and wood industries, and to a lesser degree for its leaf essential oils. The essential oils are produced commercially mainly in China, India and Brazil 1 , and are mostly used for perfumes or medicines as pain reliever 2,3 , antifungal 4,5 , allelopathic [6][7][8][9][10][11] , insect repellent agent [12][13][14][15][16] and recently as biomass feedstock for production of biofuels 17,18 . The leaf-essential oils of E. citriodora includes nearly 100 volatile compounds 1,19 , all contributing to the final lemony, rose-like odor.…”
Section: Introductionmentioning
confidence: 99%
“…PMD (para-menthane 3, 8 diol) as a repellant has a lower vapour pressure than volatile monoterpenes found in most plant oils [37] it provides very high protection from a broad range of insect vectors for several hours [36] and has a proven safety to human health.…”
Section: Discussionmentioning
confidence: 99%
“…Hill & L.A.S. Johnson (Myrtaceae) (Barasa et al 2002), pero también puede ser obtenido de otras plantas, el cual proporciona una protección de varias horas (Carroll & Laye. 2006), siendo su efecto muy similar al DEET, con un futuro prometedor en el campo de la repelencia.…”
Section: Discussionunclassified